Os impactos da contrarreforma psiquiátrica na atuação do psicólogo nos Centros de Atenção Psicossocial - Deponti, Natália Roós (2023)
The Brazilian Psychiatric Reform is historically characterized as a movement to fight against the asylum model of treatment of madness. Through various mobilizations, the Reform enabled the creation of a Psychosocial Care Network (RAPS) focused on care in freedom, with territorial devices such as the Psychosocial Care Centers (CAPS). However, studies indicate that there have always been forces against the Reform and in favor of the asylum logic, in this regard, it is observed that since 2017 such opposing forces have gained strength and have been configured as a Psychiatric Counter-Reform. Thus, it becomes important to understand this movement of setbacks and their impacts on devices derived from the Psychiatric Reform. In this sense, the present research sought to investigate the impacts of the Psychiatric Counter-Reform on the performance of professional psychologists who work in CAPS, considering that this is a profession present in services replacing asylums, since the beginning of the Psychiatric Reform. For this purpose, the study used a qualitative approach, with an exploratory character, using the technique of semi-structured interviews. Subsequently, the data was analyzed using Thematic Content Analysis. The results indicate that during the period 2017 and 2022, the asylum logic of treating madness was once again invested and valued by the active Brazilian government in this period. In addition, all professionals interviewed during the survey have the perception of a setback movement, which imposed difficulties on the RAPS, and, consequently, on the CAPS. Still, in addition to identifying the setbacks in the National Mental Health Policy, psychologists indicate some consequences of the setbacks in their daily work, such as the increase in psychiatric institutionalizations, fragmentation of work processes, isolation of teams within workspaces, outpatient clinics care, overinvestment in therapeutic communities, among other aspects. Finally, the importance of an ethical-political movement to resume the premise of the Brazilian Psychiatric Reform is understood.